Insights into the off-state breakdown mechanisms in power GaN HEMTs. (September 2019) - Zagni, N.; Puglisi, F.M.; Pavan, P.; Chini, A.; Verzellesi, G.
Abstract: We analyze the off-state, three-terminal, lateral breakdown in AlGaN/GaN HEMTs for power switching applications by comparing two-dimensional numerical device simulations with experimental data from device structures with different gate-to-drain spacing and with either undoped or Carbon-doped GaN buffer layer. Our simulations reproduce the different breakdown-voltage dependence on the gate-drain-spacing exhibited by the two types of device and attribute the breakdown to: i ) a combination of gate electron injection and source-drain punch-through in the undoped HEMTs; and ii ) avalanche generation triggered by gate electron injection in the C-doped HEMTs.